Dexmedetomidine with sufentanil in intravenous patient-controlled analgesia for relief from postoperative pain, inflammation and delirium after esophageal cancer surgery. Issue 5 (11th May 2020) - Tang, Chaoliang; Hu, Yida; Zhang, Zhetao; Wei, Zeyuan; Wang, Hongtao; Geng, Qingtian; Shi, Si; Wang, Song; Wang, Jiawu; Chai, Xiaoqing
Abstract: Background and aims: Postoperative pain can cause serious adverse reactions that severely affect postoperative outcome. The present study evaluated the effect of dexmedetomidine (DEX) added to sufentanil in intravenous patient-controlled analgesia (PCA) on the relief of pain and inflammatory responses during postoperative recovery of patients undergoing a combined thoracoscopic-laparoscopic esophagectomy (TLE). Methods: Sixty patients undergoing TLE were randomly allocated to receive 1 μg/ml of sufentanil alone (Group S) or 1 μg/ml of sufentanil plus 2.5 μg/ml of DEX (Group D) for postoperative intravenous (IV) PCA. Postoperative pain relief, cumulative PCA requirements, inflammatory marker levels, delirium and recovery were assessed. Results: A joint DEX and sufentanil regimen significantly reduced the area under the curve of numerical rating scores for pain at rest (NRSR) and coughing (NRSC) at 1–48 h postoperatively ( P = 0.000) that were associated with lower PCA-delivered cumulative sufentanil consumption and less PCA frequency until 48 h postoperatively ( P < 0.05 and P < 0.0001, respectively). The simultaneous administration of DEX and sufentanil significantly reduced plasma IL-6 and TNF-α concentrations and increased IL-10 level ( P < 0.0001, P = 0.0003 and P = 0.0345, respectively), accompanied by better postoperative delirium categories and health statuses of patients ( P = 0.024 and P < 0.05, respectively). There was no hypotension, bradycardia, respiratory depression or oversedation in Group D. Conclusion: Patients receiving DEX in addition to IV PCA sufentanil for TLE exhibited better postoperative analgesia, fewer inflammatory responses and lower postoperative delirium categories and better health statuses.